Existence Is Evidence of Immortality. (23rd April 2019) - Huemer, Michael
Abstract: The universe plausibly has an infinite future and an infinite past. Given unlimited time, every qualitative state that has ever occurred will occur again, infinitely many times. There will thus exist in the future persons arbitrarily similar to you, in any desired respects. A person sufficiently similar to you in the right respects will qualify as literally another incarnation of you. Some theories about the nature of persons rule this out; however, these theories also imply, given an infinite past, that your present existence is a probability‐zero event. Hence, your present existence is evidence against such theories of persons.